2010
DOI: 10.1186/cc9232
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-β attenuates lung inflammation following experimental subarachnoid hemorrhage

Abstract: IntroductionAneurysmal subarachnoid hemorrhage (SAH) affects relatively young people and carries a poor prognosis with a case fatality rate of 35%. One of the major systemic complications associated with SAH is acute lung injury (ALI) which occurs in up to one-third of the patients and is associated with poor outcome. ALI in SAH may be predisposed by neurogenic pulmonary edema (NPE) and inflammatory mediators. The objective of this study was to assess the immunomodulatory effects of interferon-β (IFN-β) on inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 25 publications
(24 reference statements)
3
29
0
Order By: Relevance
“…IFN-β induction during TLR3 signaling was hypothesized to be a critical component of limiting forces to immunopathologic damage (Hooks et al, 2008). Indeed, IFN-β has been reported to decrease the expression of adhesion molecules on endothelial cells (Cobelens et al, 2010;Billiau et al, 2004), monocytes (de Paus et al, 2013) and retinal pigment epithelial cells (Hooks et al, 2008) and to reduce the migration of inflammatory cells across the blood-brain barrier (Veldhuis et al, 2003;Billiau et al, 2004). In this context, it is plausible that the reduction of IFN-β expression at high doses of isobavachalcone might contribute to the loss of its inhibitory effect on NF-κB activity and ICAM-1 expression, whereas enough IFN-β might be available at low dose treatments to suppress inflammatory responses in cerebral endothelial cells stimulated with poly[I:C].…”
Section: Discussionmentioning
confidence: 99%
“…IFN-β induction during TLR3 signaling was hypothesized to be a critical component of limiting forces to immunopathologic damage (Hooks et al, 2008). Indeed, IFN-β has been reported to decrease the expression of adhesion molecules on endothelial cells (Cobelens et al, 2010;Billiau et al, 2004), monocytes (de Paus et al, 2013) and retinal pigment epithelial cells (Hooks et al, 2008) and to reduce the migration of inflammatory cells across the blood-brain barrier (Veldhuis et al, 2003;Billiau et al, 2004). In this context, it is plausible that the reduction of IFN-β expression at high doses of isobavachalcone might contribute to the loss of its inhibitory effect on NF-κB activity and ICAM-1 expression, whereas enough IFN-β might be available at low dose treatments to suppress inflammatory responses in cerebral endothelial cells stimulated with poly[I:C].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, S IOOB did not stimulate AT-Ilike cells to secrete other inflammatory mediators involved in ALI and NPE pathogenesis, such as sICAM-I, CINC-I and CINC-3 (25). One may suppose that these mediators are induced by releasing factors other than S100B orland are produced by cellular types other than AT-I cells.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, an upregulation of the soluble intercellular adhesion molecule1 (ICAM1) was found in the lungs of BD animals [29] . Similarly, Cobelens et al [31] found that experimental subarachnoid hemorrhage was associated with neutrophil influx into the lungs as well as increased expression of pulmonary adhesion molecules and chemokines. Adhesion molecules through activation, firm adhesion, and the chemotactic migration of leukocytes [32] may contribute to lung injury.…”
Section: From the Brain To The Injury Of The Lungsmentioning
confidence: 87%